Long‐distance swimming by African lions in Uganda - A. Braczkowski; L. Ochse; B. Atukwatse; O. Cornille; C. O'Bryan; P. Lindsey; R. Kotze; L. Gibson; D. Biggs (Ecology and Evolution)
Abstract Earth's most imperiled and iconic wildlife are facing tough decisions under increasing human pressure and limited resources. Swimming across rivers and water bodies filled with high densities of predators may be one such example. In African lions Panthera leo, previous water crossings (recorded in the peer‐reviewed and gray literature, on film, and found using Google Search, and YouTube) have recorded distances ranging from <10 to 100 m, with some resulting in mortality by Nile Crocodiles Crocodylis niloticus. However, we observed a coalition of male lions swimming >1 km across Uganda's Kazinga channel located in the Queen Elizabeth National Park six times, and recorded this behavior on film on February 1st 2024. We speculate that three factors could be driving these lions to take long‐distance swims with a high density of crocodiles and hippos Hippopotamus amphibius, namely (1) the lack of lionesses in this ecosystem, (2) intraspecific fights over territory with other male coalitions, and (3) the only other land connection giving lions access to the peninsula is a small road bridge with a strong human presence.